Advanced development and characterization of DEA amine-polysulfone/polyvinylacetate blend membranes - Mushtaq, A. (Maxwell Science Publications, 2014)
Membrane technology effectively separates CO2 from CH4 and has been practiced for many years but requires membranes with high selectivity and permeability. Different approaches are employed to improve membrane performance and it is soon possible to develop a blended polymeric membrane that separates high pressure gas streams at the point of processing pressure. However, glassy polymers suffer a lack of permeability causing their performance to drop as an upper bound trade-off but highly selective and rubbery polymers have high permeability with low selectivity. As an amine solution is capable of purifying naturally acidic gas, blending glassy, rubbery polymers with amines-specifically, polysulfone and polyvinyl acetate with diethanol amine in dimethyl acetamide as solvent-we developed flat sheet membranes with desirable properties. As it is now possible to acquire amine-polymer blends with more desirable properties by mixing with a miscible polymer, it is essential to observe factors that affect the polymer's miscibility with amines. Hence, we also analyzed the effects of blend ratios on different properties. Blended membranes of different ratios were synthesized and their functional groups were characterized by Fourier Transformed Infra-Red spectroscopy (FTIR). We then employed Thermal Gravimetric Analysis (TGA) to describe weight loss and Field Emission Scanning Electron Microscopy (FESEM) to determine respective morphologies. Â© Maxwell Scientific Organization, 2014.